Estudo da Estrutura da Proteína SH do Vírus Sincicial Respiratório Humano: análise funcional da estrutura pentamérica por ferramentas de bioinformática - Araujo, Gabriela Campos de [UNESP] (2013)
The human Respiratory Syncytial Virus (hRSV) is the major cause of lower respiratory tract illnesses in children and elderly people worldwide. Its genome encodes 11 proteins including the surface protein F, G and SH which are responsible for entry and distribution of virus in the host cell. Among the protein surface, little is known about the function of protein SH. Knowing their structure and function is fundamental to a better understanding of its mechanism. The aim of this study was modeling and caracterization of the RSV SH protein and analysis of structural behavior in different environment : water and phopholipid bilayer for understanding and evaluating the formation of its pentameric structure. The SH protein model was generated by I-TASSER server, and its funcional and structural caracterisct was analyzed by PredictProtein and PsiPred. Molecular Dynimics Simulation were performed for analysis of hidrophobicit of protein central region, studies of the protein behavior on the membrane and pentamer formation. The SH protein model prediction resulted in a linear model with a helix-alpha between amino acid 20-42 and the anlysis performed by PsiPred indicated this region as transmembrane region. Molecular Dynamics Simulation showed that, when in solution,the proteína changes its linear conformations for globular conformation confirming the hydrophobicity of the central domain. The presence of the Sh protein itself or of the pentamer in bilayer resulted in a considerable decrease of the area per lipid, giving the chains less mobility and greater alignment. The pentamer simulation showed passage of water molecules through the pore in an environment where histidine residues H22 and H51 are protonated, indicating the dependence of this activity with the pH of the medium. Based on this analysis, it was proposed the structure tertiary and quaternary of the SH protein and, with the analysis of the ...